Preschool abilities of children born preterm and low weight - Sasha A. Martínez-Espiet; Irene Sumaza Laborde; Leila Crespo Fernández; Maribel Campos Rivera; Frances Boulon Díaz (Interacciones)
The purpose of this study was to evaluate the development among a group of pre-school children born premature and with low weight. We evaluated a group of four years old children; 20 children born prematurely and 20 children born after a full gestation and desired weight, using the Beery-Buktenica visual-motor integration test. We also administered the Ages and Stages Questionnaire (ASQ-3) development test to all 40 mothers. Statistical analysis was performed using student t test for independent groups. The group of children born prematurely scored significantly lower on tests measuring visual perception skills (µ1 83.65 ; µ2 93.7) (p = 0.0001), visual-motor integration (µ1 93.6 ; µ2 104.8) (p = 0.001) and fine motor (µ1 36.00 ; µ2 44.25) (p=0.033) (p = 0.033), when compared to the group of children born after a full term. This study suggests that premature low weight born children have lower performance in the sensory-motor development during the preschool years. These disadvantages go unnoticed and may represent future delays on school tasks that require these skills. It is important to promote an early assessment and environmental stimulation among this population even in the absence of risk indicators.